Study on Oxygen Reduction Method of Phosphorus-doped Hydrogenated Nano-silicon. Issue 2 (April 2021) - Liu, Danjuan; He, Wei
Abstract: In recent years, hydrogenated nano-silicon has attracted much attention due to its high specific energy density. However, the slow kinetic oxygen reduction reaction (ORR) and oxygen evolution reaction (ORE) reduce the efficiency of hydrogenation of nano-silicon and hinder its practical application. The development of non-precious catalysts with excellent performance and low price is of great significance to the development of hydrogenated nano-silicon. Among many hydrogenation nano-silicon catalysts, cobalt-based compounds have good ORR and ORE catalytic performance, and are rich in Co reserves and low in price. Especially doped compounds have excellent stability. In the thesis, three series of hydrogenated nano-silicon composite materials of Co-SrCO3/NC, Co-Nd/NC and Co-Ce/NC were successfully synthesized through heating reflow method and subsequent high-temperature calcination. XRD, Raman, XPS, TEM, nitrogen isothermal adsorption and desorption and other analytical methods were used to characterize the structure of the above composite materials. Through chemical tests, the composite materials were evaluated for the catalytic performance of ORR and ERR, and their structure-activity relationship was analyzed. The Co_SrC03/NC series composite materials were calcined at different temperatures. The results showed that the generated SrCO3 nanorods were embedded in the graphite shell and contacted with hydrogenated nano-silicon. In an oxygen-saturated 0.1MKOH solution, Co-SrCO3/NC series composites have excellent ORR/ORE catalytic activity, especially Co-SrCO3/NC-600 has more stable activity than precious metal catalysts of 20wt% Pt/C and Ir02. Sex. The air prepared with Co-SrCO3/NC-600 has better performance. During the in-depth study of 10mA_cnT2, Co-SrC03/NC-600 was used as the air to maintain a stable platform of 1.10V, and the platform of 20wt%Pt/C under the same conditions was 1.17V.